Memory Islands -- Ontology display - Ganascia, Jean-Gabriel (2012)
With the concept of Memory Islands, the ACASA team propose a new tree visualization approach that is based on cartography, i.e. on a spatialization of abstract data structures, mainly trees. The hypothesis on which the notion Memory Island is based is that the spatialization helps to memorize contents. This notion of Memory Island is applied to ontology visualization, which could help to access to many online documents.